2006
DOI: 10.1093/jxb/erl107
|View full text |Cite
|
Sign up to set email alerts
|

A fluoroorotic acid-resistant mutant of Arabidopsis defective in the uptake of uracil

Abstract: A fluoroorotic acid (FOA)-resistant mutant of Arabidopsis thaliana was isolated by screening M2 populations of ethyl methane sulphonate (EMS)-mutagenized Columbia seed. FOA resistance was due to a nuclear recessive gene, for1-1, which locates to a 519 kb region in chromosome 5. Assays of key regulatory enzymes in de novo pyrimidine synthesis (uridine monophosphate synthase) and salvage biochemistry (thymidine kinase) confirmed that FOA resistance in for1-1/for1-1 plants was not due to altered enzymatic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Studies using radiolabelled purins, pirimidines and [ 14 C] fluoroorotic acid revealed that the FOA recessive genes for “1-1/for 1-1” on chromosome 5 were unable to uptake uracil or uracil-like bases in Arabidopsis thaliana mutant [123].…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using radiolabelled purins, pirimidines and [ 14 C] fluoroorotic acid revealed that the FOA recessive genes for “1-1/for 1-1” on chromosome 5 were unable to uptake uracil or uracil-like bases in Arabidopsis thaliana mutant [123].…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 99%
“…To date, six loci along chromosome 5 of Arabidopsis genome were identified to encode nucleobase transporters: At5g03555 (from PRT family); At5g25420, At5g49990, and At5g62890 (from NAT family); At5g50300 (an AzgA-like transporter); and At5g41160 (from PUP family) [123], [124]. The recently characterized AzgA adenine–guanine–hypoxanthine transporter of Aspergillus nidulans was found to have amino acid similarity to Arabidopsis loci At5g50300 and At3g10960 encode proteins [125].…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cells in all domains of life possess specific nucleobase transporters, distinct from those involved in the uptake of nucleosides (1,2). Nucleobase transporters are important in protozoan and plant development and in the susceptibility of human, protozoan, or fungal cells to purine-related drugs (3)(4)(5)(6)(7)(8)(9)(10). Fungi possess three evolutionary distinct families of transporters specific for nucleobases (2,11,12).…”
mentioning
confidence: 99%
“…In a screen for fluoroorotic acid (FOA)‐resistant plants, the for1 mutant was identified. Uptake studies using radiolabelled purines, pyrimidines and [ 14 C]‐FOA reveal that for1 plants were specifically defective in the uptake of uracil or uracil‐like bases (Mourad et al. 2006).…”
Section: Nucleobase Transportmentioning
confidence: 99%